Tool kits for the Sustainable Management of Ghana’s Riverine Biodiversity: an Overview - Gordon, C.; Linstead, C.; Moss, B.; Ansa-Asare, O.; Annang, T.; Leah, R.; Kyerematen, R.; Owusu, E.H.; Maltby, E.; Bissaw, M.; Ampomah, B. (West African Journal of Applied Ecology, 2012)
The Darwin Initiative funded project Tool kits for the Sustainable Management of Ghana’s Riverine Biodiversity was a collaboration between the Centre for African Wetlands at the University of Ghana, various units of the University of Ghana and the Ghana Wildlife Society. The project also involved collaborators from Burkina Faso, Nigeria, Cote d’Ivoire, Togo and Benin. The project aimed to address the impediments that remain for Ghana (and its neighbouring countries) in applying the Ecosystem Approach (EA) to riverine wetland management and the delivery of the Convention on Biodiversity (CBD). Priority needs were identified as taxonomic capacity building, a contemporary assessment of the status of aquatic biodiversity in Ghana, the development of practical management tools for rivers and increased engagement of stakeholders in decision-making together with an enhanced environmental awareness throughout Ghanaian society. These were addressed in this project by regional and local staff training, reporting on the current status of aquatic communities, the production of educational and taxonomic resources for a range of users, the development of a set of nested indicators of ecosystem health adapted for use at various levels, and the production of a policy document outlining the means of applying the EA in the management of Ghana’s rivers.
Keywords: Aquatic Resource management; Descision Support Mechanisms; Biodiversity; Ghana